Types extent of pathology and ossicular status in atticoantral disease undergoing mastoid exploration at TUTH. - Thapa, Narmaya
SUMMARY: This prospective study was carried out at the department of Otorhinolaryngology and Head &Neck Surgery, TUTH, Maharajgunj from March 1998 to March 1999. The aims of the study were to find out types of pathology, extent of ossiscular damage and to correlate types of pathology with extent of ossicular damage in cases with CSOM attioantral type undergoing mastoid exploration. The study comprised of 108 cases. After admission brief history regarding duration and nature ear discharge, and history of previous ear surgery was taken. Otoscopic examination was done in each patient and the findings were confirmed by EUM during surgery. Peroperative types of disease, their extent and the status of ossicles were noted. Age of the patient varied from6-69 years with mean age of 20.7years (+_9.14 SD). Male patients were 69 (63.89%) compared to female patients 39 (36.11%). Posterosuperior quadrant 54 (50%) was the common site of disease in EUM. Peroperatively, 91(84.26%) had cholesteatoma whereas 17 (15.74%) had granulation tissue only. Of 108 cases, 2(1.85%) had group 1 disease, 12 (11.11%) had group 2 disease, 5(4.63%) had group 3, 35 (32.41%) had group 4,8 (7.41%) had group 5 and 46 (42.59%) had group 6 disease. This indicated tjat majority of patients with CSOM AA had extensive disease. Only 12( 11.11%) cases had intact ossicles, 10 (9.26%) had no ossicles and 86(79.63%) had partly necrosed ossiculur chain. Incus was the commonly affected ossicle. Lenticulur process of incus 86 (80.57%) and short process of mallcus 16( 14.81%) respectively were the most and least affected parts of ossiculur chain, In 79 (86.96%) cholesteatomatous cases and in 17(100%) cases with granulation tissue ossicles were damaged wholly or partly. M+ S+ ossiculur defect 45 (41.67%) was the commonest in both cholesteatomatous and granulation tissue cases.